Access Differentials in Primary Healthcare among Vulnerable Populations in a Health Insurance Setting in Kumasi Metropolis, Ghana: A Cross-Sectional Study. (27th July 2021) - Acquah-Hagan, Gertrude; Boateng, Daniel; Appiah-Brempong, Emmanuel; Twum, Peter; Atta, Joseph Amankwa; Agyei-Baffour, Peter
Abstract : Background . Access to healthcare remains a challenge towards the achievement of the Sustainable Development Goals in Ghana. There still remain inequalities in the distribution of health services especially among vulnerable groups despite sustained efforts to strengthen the health system. This study was conducted to analyze access differentials among different vulnerable groups in the context of primary healthcare under a National Health Insurance Scheme (NHIS) in Ghana. Methods . This study was a descriptive cross-sectional study conducted among multilevel participants of vulnerable groups in Kumasi Metropolis: 710 vulnerable people constituting elderly/aged ( n  = 359), pregnant women ( n  = 117), head poters (teenage girls who migrated from the northern Ghana mainly to the capital cities of the Ashanti and Greater Accra region to help in carrying of goods for their livelihood) ( n  = 86), sex workers ( n  = 75), and other vulnerable groups (people with disabilities and street participants) ( n  = 73). Data were collected using a semistructured questionnaire. Poisson regression with robust variance was used to access the association between vulnerability and access to healthcare. Results . Close to a fifth, 18.5% of the study respondents were unable to access care at any point in time during the last 12 months. Reasons for the inability to access healthcare included limited funding (69.7%), poor attitude of service providers (7.6%), distance to health centers (8.3%), and religious reasons (6.2%). More than 95% of respondents were insured under the NHIS, but acceptability of service provision under the NHIS was low among the vulnerable groups. In the crude models, pregnant women had lower prevalence of access to medications as compared to the elderly (prevalence ratio (PR): 0.88; 95% CI: 0.80–0.98). Head poters and other vulnerable groups were also less likely to view healthcare as affordable as compared to the elderly. The differences in healthcare access observed were attenuated after adjustment for sociodemographic characteristics and healthcare-related factors. Conclusions . Despite the introduction of a NHIS in Ghana, this study highlights challenges in healthcare access among vulnerable populations independent of the type of vulnerability. This suggests the need for stakeholders to work to address access differentials in the NHIS and adopt other innovative care strategies that may have broader applicability for all populations.